2015
DOI: 10.1149/2.0171504jes
|View full text |Cite
|
Sign up to set email alerts
|

Film Breakdown and Nano-Porous Mg(OH)2Formation from Corrosion of Magnesium Alloys in Salt Solutions

Abstract: Small angle neutron scattering (SANS) and scanning transmission electron microscopy (STEM) were used to study film formation by magnesium alloys AZ31B (Mg-3Al-1Zn base) and ZE10A (Elektron 717, E717: Mg-1Zn + Nd, Zr) in H 2 O and D 2 O with and without 1 or 5 wt% NaCl. No SANS scattering changes were observed after 24 h D 2 O or H 2 O exposures compared with as-received (unreacted) alloy, consistent with relatively dense MgO-base film formation. However, exposure to 5 wt% NaCl resulted in accelerated corrosion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
92
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(105 citation statements)
references
References 72 publications
12
92
0
1
Order By: Relevance
“…The film was non-uniform in thickness, typical of the aqueous corrosion of Mg alloys (especially in the presence of NaCl). 16,[20][21][22]28,[31][32][33]35,36,45,47,66 The film structure was complex, but generally morphologically duplex, with an overall "convex appearing" outer film region that consisted of a fine layered/striated morphology varying in total thickness on the order of ∼10-100 nm thick, overlying an inner, nodular-like film extending inward ∼0.5 to 1 μm for the location imaged. The outer convex film likely corresponded with the smooth, globular features evident in the secondary electron surface image shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The film was non-uniform in thickness, typical of the aqueous corrosion of Mg alloys (especially in the presence of NaCl). 16,[20][21][22]28,[31][32][33]35,36,45,47,66 The film structure was complex, but generally morphologically duplex, with an overall "convex appearing" outer film region that consisted of a fine layered/striated morphology varying in total thickness on the order of ∼10-100 nm thick, overlying an inner, nodular-like film extending inward ∼0.5 to 1 μm for the location imaged. The outer convex film likely corresponded with the smooth, globular features evident in the secondary electron surface image shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Refs. 16,22,24,35,44). The rough surface and undulating, nonuniform nature of the films formed in the 20 h 2 nd step 0.01 wt% NaCl exposure resulted in very diffuse transitions between film and metal in the SIMS data (Figs.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The theoretically calculated surface energies of Mg (0001), and (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) 33 A higher surface energy can result in an increased dissolution rate. The theoretical dissolution rates of Mg crystallographic planes (10-10) and (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) are predicted to be about 18-20 times higher than that of the basal plane (0001). 34 A corrosion study on a hcp Zn single crystal showed that the corrosion resistance of the (0001) basal plane is about 1.4 times that of the (1120) and (1010) planes in 1 M (NH 4 ) 2 SO 4 .…”
Section: Discussionmentioning
confidence: 99%
“…19,[22][23][24][25][26] Cathodically active sites have been examined through the use of scanning vibrating electrode technique (SVET) on 99.9% 25 and 99.99% 23 pure Mg, Mg-Nd binary alloys 24 and AZ31. 22,27 To date, mechanisms have been proposed, which explain this behavior, including: (i) transition metal enrichment from impurities, 28,29 (ii) particle enrichment to the oxide layer 26,30,31 and (iii) Al redeposition. 30 Evidence of cathodic activation has been noted to also be influenced by cathodic sites upon the Mg sample surface, namely intermetallic particles (IMPs) and impurities.…”
mentioning
confidence: 99%